Getting history right : East and West German collective memories of the Holocaust and war - Wolfgram, Mark A. 1970- (Bucknell University Press, 2011)
Collective memory, politics, and culture -- Victims and perpetrators : the view from the East -- Victims and perpetrators : the view from the West -- Collaboration and resistance : blood and redemption -- Division and unity : a revolutionary people unites itself -- Defeat and liberation : ending the war -- Conclusion--Mourning, loss, and the difficulty of remembering -- Appendix: Charts and chart notes -- Filmography